PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia) - Kusumaningrum, Diyah Putri; Iswara, Ulfah Setia (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2022)
This research aimed to examine and analyze independent variables consisting of profitability, leverage, and firm size; on the dependent variable namely, firm value. The profitability was measured by Return On Asset (ROA), leverage was measured by Debt to Equity Ratio (DER), and firm size was measured by SIZE. Meanwhile, the firm value was measured by Price Book Value (PBV). The population was Food and Beverage companies that were listed on Indonesia Stock Exchange (IDX) during 2017-2021. The research was quantitative. Furthermore, the data collection technique used purposive sampling. In line with that, there were 14 companies as the sample and 70 data of observations. Additionally, the data analysis technique used multiple linear analysis. The result concluded that (a) profitability had a positive effect on firm value. It meant, that with good profitability, the companies could become a good prospect for investors in the future. Likewise, (b) leverage had a positive effect on firm value. This meant that higher leverage would increase the firm value which the investors liked. However, (c) firm size did not affect firm value since it could not be a profit consideration within companies.